Super Gas Barrier and Fire Resistance of Nanoplatelet/Nanofibril Multilayer Thin Films. Issue 2 (16th November 2018) - Qin, Shuang; Pour, Maryam Ghanad; Lazar, Simone; Köklükaya, Oruç; Gerringer, Joseph; Song, Yixuan; Wågberg, Lars; Grunlan, Jaime C.
Abstract: Cellulose nanofibrils (CNF) are abundant in the fiber cell walls of many plants and are considered a nearly inexhaustible resource. With the goal of improving the flame resistance and gas barrier properties of cellulose‐based films, cationic CNF are assembled with anionic vermiculite (VMT) clay using the layer‐by‐layer deposition process. The highly aligned VMT nanoplatelets, together with cellulose nanofibrils, form a nanobrick wall structure that exhibits high optical transparency, flame resistance, super oxygen barrier, and high modulus. A 20 CNF/VMT bilayer (BL) nanocoating, with a thickness of only 136 nm, exhibits an oxygen transmission rate of 0.013 cc (m 2 day atm) –1 . With only 2 BL of CNF/VMT, the melting of flexible polyurethane foam exposed to a butane torch is prevented. These nanocoatings also exhibit a high elastic modulus (20 GPa) and hardness (1 GPa). This study demonstrates a unique, renewable, cellulose‐based nanocoating that could be used in a variety of packaging and protection applications. Abstract : Layer‐by‐layer assembled cellulose nanofibril/vermiculite nanocoatings demonstrate improved gas barrier, flame resistance, and mechanical properties. A 136 nm thick coating imparts a 100× better oxygen transmission rate (0.013 cc (m 2 day atm) –1 ) on a 179 µm polyethylene terephthalate; and the melting of flexible polyurethane foam is completely prevented. These environmentally benign and low‐cost coatings are useful for various packaging and protection applications.